Analysis of Risk Factors for the Development of Gestational Diabetes Mellitus in a Group of Romanian Patients. (2nd June 2022) - Preda, Agnesa; Stefan, Adela Gabriela; Vladu, Ionela Mihaela; Fortofoiu, Mircea-Catalin; Clenciu, Diana; Fortofoiu, Maria; Gheorghe, Ioan Ovidiu; Comanescu, Alexandru Cristian; Mota, Maria
Abstract : Introduction . Gestational diabetes mellitus (GDM) is caused by numerous risk factors, the most common being old age, obesity, family history of diabetes mellitus, GDM, history of fetal macrosomia, history of polycystic ovary syndrome or treatment with particular drugs, multiple births, and certain races. The study proposed to analyze the risk factors causing GDM. Method . In the study, we included 97 pregnant women to whom there was an OGTT performed between weeks 24th and 28th of pregnancy, divided into two groups, with GDM and without GDM. The statistical analysis was performed with SPSS 26.0, the tests being statistically significant if p value < 0.05. Results . The favoring risk factors for the onset of GDM were analyzed, with statistically significant differences between the GDM group and the group without GDM related to the delivery age (32.39 ± 4.66 years old vs. 28.61 ± 4.71 years old), history of fetal macrosomia (13.7% vs. 0%), presence of GDM during previous pregnancies (7.8% vs. 0%), HBP before pregnancy (9.8% vs. 0%), gestational HBP (17.6% vs. 0%), glycemia value at first medical visit (79.37 ± 9.34 mg / dl vs. 71.39 ± 9.16 mg / dl ), and weight gain during pregnancy (14.61 ± 4.47 kg vs. 12.48 ± 5.87 kg ). Conclusions . Identifying the risk factors for the GDM onset has a special importance, implying an early implementation of interventional measures in order to avoid the onset of GDM and associated maternal and fetal complications.